FACTORS RELATED TO ANXIETY LEVEL IN ELDERLY RETIREMENTS IN SEROJA PUSKESMAS, BEKASI CITY 2022 - Hanna Rada Soraya; Riris Ocktryna Silitonga; Nurti Y. K. Gea (Jurnal Medicare, 2024)
Background: Aging is a process of slowly disappearing – gradually the ability of tissues to repair themselves or maintain their normal function so that they cannot survive the infection and repair the damage suffered. Anxiety the appearance of a fear or worry in something unclear and related to feelings of uncertainty and helplessness Factors causinganxiety in the elderly . Internal factors (biological, psychological, socio-cultural) : external factors (gender, age, social support, economic status). Researcher's Objective:Knowing the factors related to the level of anxiety in the retired elderly at the Seroja Kota Bekasi Health Center 2022. Research Method: The design in this study used Observational Analytics with a Cross Sectional research design, using independent variables of factors causing elderly packaging and a type of random sampling with a total sample of 88 respondents. The instruments in this research used digital questionnaires and interviews and were conducted using Chi Square. Researcher results:Based on statistical analysis with a significance level of 95% or a α value (0.05) chi square test results obtained p value (0.562) > α value (0.05) the results did not have a significant relationship between sex and anxiety level in respondents this showed Ha was rejected, 95% significance level or α value (0.05) Chi Square test results obtained p value (0.134) > α value (0.05) so that it can be concluded from these results there is no significant relationship between age and anxiety level in respondents this shows Ha is rejected, a significance level of 95% or a α value (0.05) chi square test results obtained p value (0.000) < α value (0.05) so that it can be concluded from these results there is a relationship between economic status and anxiety level in respondents this shows H0 is rejected, with a significance level of 95% or a value of α (0.05) chi square test results obtained p value (0.000) < value α (0.05) so that it can be concluded from these results there is a relationship between family support and the level of anxiety in respondents this shows that H0 is rejected. Thus it can be interpreted that "factors related to the level of anxiety in elderly retirees at the Seroja K Health Center ota Bekasi 2022". Conclusion: there is a relationship and there is no relationship between external factors, the level of anxiety level in the retired elderly at the Bekasi Health Center 2022.